فعالية برنامج قائم على اللعب الجماعي لتنمية مهارات التواصل لدى الأطفال ذوي اضطراب التوحد وأثره في تحسين التفاعل الاجتماعي لديهم - بيومي، لمياء عبدالحميد (جامعة الإسكندرية - كلية رياض الأطفال, 2020)
هدف البحث إلى التعرف على فعالية برنامج قائم على اللعب الجماعي لتنمية مهارات التواصل لدى الأطفال ذوى اضطراب التوحد وأثره في تحسين التفاعل الاجتماعي لديهم، وقد تم استخدام المنهج شبه التجريبي لتحقيق أهداف البحث، والحصول على عينة بلغت (16) طفلة من ذوى اضطراب التوحد لديهم قصور في مهارات التواصل وتم تقسيمهن إلى مجموعتين متكافئتين: (التجريبية ن= 8 والضابطة ن= 8) والتحقق من تكافؤ المجموعتين في كل من العمر، والذكاء ومهارات التواصل والتفاعل الاجتماعي، وكانت أدوات البحث مقياس مهارات التواصل ومقياس التفاعل الاجتماعي، وبناء برنامج قائم على اللعب الجماعي، وانتهت النتائج إلى وجود فروق ذات دلالة إحصائيا بين المجموعتين (التجريبية والضابطة) في القياس البعدي لأبعاد مقياس مهارات التواصل والدرجة الكلية من حيث تحسن مهارات التواصل لصالح المجموعة التجريبية، ووجود فروق ذات دلالة إحصائية بين المجموعتين (التجريبية والضابطة) في القياس البعدي لأبعاد مقياس التفاعل الاجتماعي والدرجة الكلية من حيث تحسن التفاعل الاجتماعي لديهم لصالح المجموعة التجريبية، أيضا وجود فروق دالة إحصائيا بين القياسين القبلي والبعدي للمجموعة التجريبية لأبعاد مقياس مهارات التواصل والدرجة الكلية لصالح القياس البعدي، ووجود فروق دالة إحصائيا بين القياسين القبلي والبعدي للمجموعة التجريبية لأبعاد مقياس التفاعل الاجتماعي والدرجة الكلية لصالح القياس البعدي، عدم وجود فروق ذات دلالة إحصائية بين القياسين البعدي والتتبعي للمجموعة التجريبية لأبعاد مقياس مهارات التواصل والدرجة الكلية ولا توجد فروق دالة إحصائيا بين القياسين البعدي والتتبعي للمجموعة التجريبية لأبعاد مقياس التفاعل الاجتماعي والدرجة الكلية، وأوصى البحث ببعض التوصيات والمقترحات البحثية.
The current research aims to identify the effectiveness of a program based on group play to develop communication skills in children with autism disorder and its impact in improving their social interaction.. To achieve this goal, a quasi- experimental approach was used, and a sample was (16) children with autism who have lack in communication skills, and they were divided into two equal groups: (experimental n = 8 and control n = 8) and verifying the equivalence of the two groups in both age, intelligence and communication and social interaction skills. The research tools were a measure of communication skills, a measure of social interaction, and building a group play- based program. The results were there are a statistically significant differences between the two groups (experimental and control) in the post- measurement of the dimensions of the communication skills scale and the total score in terms of improving communication skills in favor of the experimental group, there are a statistically significant differences between the two groups (experimental and control) in the post- measurement for the dimensions of the social interaction scale and the total score in terms of improving their social interaction in favor of the experimental group, there are a statistically significant differences between the two groups (experimental and control) in the post- measurement for the dimensions of the communication skills scale and the total score in favor of the post measurement, there are a statistically significant differences between the two measurements, pre and post, of the experimental group for the dimensions of the social interaction scale and the total score in favor of the post measurement, there are also no statistically significant differences between the post and follow up measures of the experimental group for the dimensions of the skills communication scale and total score, and there are no statistically significant differences between the post and follow up measures of the experimental group for the dimensions of the social interaction scale and the total score. The research recommended some research recommendations and proposal.
Keywords: البرامج التعليمية -- اللعب الجماعى -- المهارات التواصلية -- التفاعل الاجتماعي -- اضطراب التوحد